Effect of SiC Nanowhisker on the Microstructure and Mechanical Properties of WC-Ni Cemented Carbide Prepared by Spark Plasma Sintering - Xiaoyong Ren; Zhijian Peng; Zhiqiang Fu; Chengbiao Wang (The Scientific World Journal)
Ultrafine tungsten carbide-nickel (WC-Ni) cemented carbides with varied fractions of silicon carbide (SiC) nanowhisker (0–3.75 wt.%) were fabricated by spark plasma sintering at 1350°C under a uniaxial pressure of 50 MPa with the assistance of vanadium carbide (VC) and tantalum carbide (TaC) as WC grain growth inhibitors. The effects of SiC nanowhisker on the microstructure and mechanical properties of the as-prepared WC-Ni cemented carbides were investigated. X-ray diffraction analysis revealed that during spark plasma sintering (SPS) Ni may react with the applied SiC nanowhisker, forming Ni2Si and graphite. Scanning electron microscopy examination indicated that, with the addition of SiC nanowhisker, the average WC grain size decreased from 400 to 350 nm. However, with the additional fractions of SiC nanowhisker, more and more Si-rich aggregates appeared. With the increase in the added fraction of SiC nanowhisker, the Vickers hardness of the samples initially increased and then decreased, reaching its maximum of about 24.9 GPa when 0.75 wt.% SiC nanowhisker was added. However, the flexural strength of the sample gradually decreased with increasing addition fraction of SiC nanowhisker.